Low performance of vitamin C compared to ammonium chloride as an urinary acidifier in feedlot lambs - Laurenti Ferreira, Danilo Otávio; Santarosa, Bianca Paola; Sacco Surian, Soraya Regina; Takahira, Regina Kiomi [UNESP]; Chiacchio, Simone Biagio [UNESP]; Amorim, Rogério Martins [UNESP]; Dias, Adriano [UNESP]; Gonçalves, Roberto Calderon [UNESP] (FapUNIFESP (SciELO), 2020)
Obstructive urolithiasis is highly prevalent disease in feedlot sheep. Urinary acidification is effective for disease prevention. Forty-five healthy 3-4 month-old male Santa Inês crossbred feedlot lambs were distributed into three groups of 15 animals each. Ammonium chloride (GA) at 400 mg/ kg/day/animal, vitamin C (GC) at 4 mg/kg/day/animal, and a combination of the two (GAC) were administered orally for 21 d. Blood and urine samples were taken 7 d before beginning treatment (M0), immediately before (M1), and weekly for 21 d (M2, M3, and M4) for renal function tests, levels of Ca, P, and Mg in serum and urine, urinalysis, and fractional excretion (FE) analysis in these minerals. In groups GA and GAC, pH decreased in M2 and remained acidic throughout the experiment. A significant decrease in serum P and a urinary increase in Ca and Mg occurred in GA. The FE of Ca increased during treatments, but there was no interference with Mg. The FE of P was significantly lower in GA. Ammonium chloride was an effective urinary acidifier in sheep, but vitamin C administered orally did not provide stable results. Thus, based on our results, vitamin C supplementation may not effective for urinary acidification to prevent obstructive urolithiasis.
Baixo desempenho da vitamina C comparado ao cloreto de amônio como acidificante urinário em cordeiros confinados
Keywords: Fractional excretion; PH urinary; Small ruminants; Urinalysis; Urolithiasis